Pengaruh Vitamin B Kompleks Pada Produksi Senyawa Antimicrobial Peptides dari Pediococcus pentosaceus Serta Uji Aktivitasnya Terhadap Bacillus cereus dan Eschericia coli - Febrianty, Debby Ananda; Wijanarka, W; Rukmi, Isworo (Bioma : Berkala Ilmiah Biologi, 2021)
Both eukaryotic and prokaryotic organisms can produce antimicrobial peptides (AMPs) which function as a self-defense mechanism against other harmful organisms in the same ecological niche. Pediococcus pentosaceus is a species of Lactic Acid Bacteria (LAB) capable of producing AMPs in the form of bacteriocins and bacterocin-like inhibitory substances. The compounds it produces have received Generally Regarded as Safe status by the Food and Drug Association (FDA) and have potential as biological preservatives in the food sector. The production of these compounds can be influenced by environmental factors and growth medium of producing bacteria, so that optimization studies for the production of bacteriocin have been developed, in order to obtain optimal its activity. Vitamin B Complex is one of the growth factors needed by living things including bacteria to support their metabolism. This study aims to determine whether the addition of vitamin B complex affects the production and activity of AMPs from P. pentosaceus. Vitamin B Complex concentrations of 0 ppm, 0.1 ppm, 1 ppm and 10 ppm were added to the production medium of P. pentosaceus. Cell-free supernatants were harvested by centrifugation, then their activity was tested against Bacillus cereus and Eschericia coli using the Kirby Bauer method and analyzed using one way ANOVA parametric statistical test with a significance level of 0.05 and Duncan's post hoc test. The results showed that the addition of vitamin B complex was not significantly different to the activity of AMPs compounds, but in higher concentrations could reduce the activity of these compounds.